Citizenship in Multicultural Communities in the South of Russia - Lubsky, Anatoly V.; Shevchenko, Olga M.; Volkov, Yuriy G.; Bineeva, Natalia K.; Vagina, Viktoria O. (Journal of History Culture and Art Research, 2019)
The study deals with the analysis of citizenship as a perception, value, and attitude in mental programs of various social groups, determining their civic behavior in regional communities in the south of Russia. Characteristic aspects of citizenship as an attitude in the structure of mental programs determine civic practices involving the participation of respondents in civic initiatives and resolution of social problems. The methodological basis of the study of citizenship in regional communities in the south of Russia consists of a multidisciplinary approach that allows using information that was obtained in various fields of scientific knowledge. The multidimensional methodological construct of social research of the structure of mental programs as a set of perceptions, values, and attitudes that determine the civic engagement of various social groups is methodologically important for the study of characteristic aspects of citizenship. Findings of social research into perceptions of citizenship established in regional communities in the south of Russia, serve as an empirical basis. In the course of the study, the authors conclude that regional communities in the south of Russia are lacking a stable attitude towards civic participation, which allows drawing a conclusion about the low level of formedness of the culture of civic participation. The reason for social inertia consists of, first, the lack of belief in the effectiveness of joint civic activity in the majority of the population, second, in the lack of social trust in the regions of the South of Russia. Findings obtained allow us to understand the reasons for the low level of development of civic engagement in regional communities, which stem from etatist and paternalistic structures of mental programs impeding the formation of civic society institutions in multi-ethnic regions of the South of Russia.